(untitled) (Research, Society and Development, 2020)
Sepsis is considered to be one of the most fatal diseases worldwide. It is a disease of high morbidity and mortality, which treatment involves high costs and demands a service of excellence in the emergency and intensive care units. Objective: describe the nursing care in the detection of signs and symptoms of sepsis. Methodology: The study was designed through a bibliographical review using studies of the last ten years. A search was performed in the Virtual Health Library (VHL) in 2019, as well as in the databases: Bireme, Lilacs and Scielo, with the following descriptors: "sepsis", "nursing care", "intensive care". Results: The national scenario pointed out that patients with sepsis or septic shock, causing 55% of these patients to die, occupy approximately 30% of ICU beds in Brazil. Conclusion: The nursing professional works by offering all the necessary support, using their scientific knowledge so that the care is individualized and directed to the real needs of the individual.